Hush! a Thai lullaby - Ho, Minfong; Meade, Holly (New York Orchard Books, 1996)
A lullaby which asks animals such as a lizard, monkey, and water-buffalo to be quiet and not disturb the sleeping baby.
Keywords: Lullabies, English -- United States; Lullabies; American poetry; Thailand -- Juvenile poetry; Thailand -- Poetry